2012
DOI: 10.2139/ssrn.2080285
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Euro-Area Yield Curve with Discrete Policy Rates

Abstract: This paper presents a no-arbitrage model of the yield curve that explicitly incorporates the central-bank policy rate. After having estimated the model using daily euro-area data, I explore the behaviour of risk premia at the short end of the yield curve. These risk premia are neglected by the widely-used practice that consists in backing out market forecasts of future policy-rate moves from moneymarket forward rates. The results suggest that this practice is valid in terms of sign of the expected target moves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This application illustrates how the flexibility of the short-term rate's specification given in (3.16) can be exploited in order to construct a term-structure model where the central-bank policy rate plays a central role. The main features and results of the model are reported here; a complete study can be found in Renne (2012).…”
Section: A Multi-regime Model: the Euro-area Yield Curve With Discretmentioning
confidence: 99%
See 1 more Smart Citation
“…This application illustrates how the flexibility of the short-term rate's specification given in (3.16) can be exploited in order to construct a term-structure model where the central-bank policy rate plays a central role. The main features and results of the model are reported here; a complete study can be found in Renne (2012).…”
Section: A Multi-regime Model: the Euro-area Yield Curve With Discretmentioning
confidence: 99%
“…If one wants to model the overnight-indexed swap yield curve, the shortest-term (overnight) interest rate to consider is not the policy rate but the interbank rate, which is called EONIA (Euro Over-Night Index Average) in the euro area and denoted by r t . Therefore, Renne (2012) introduces in the model a specification of the so-called EONIA spread, that is the spread between the euro-area overnight interbank rate and the policy rate. The evolution of this spread is displayed in Panel B of Figure 2.…”
Section: A Multi-regime Model: the Euro-area Yield Curve With Discretmentioning
confidence: 99%